2014
DOI: 10.5539/jas.v6n4p19
|View full text |Cite
|
Sign up to set email alerts
|

Results of Rearing Broiler Chickens Under Various Systems

Abstract: The aim of the study was comparison of the results of rearing broilers kept under intensive and semi-intensive systems, fed with complete feeds with an addition of various proportions of wheat grain. The study was carried out on 100 broilers, HUBBARD -FLEX, of both sexes. The birds were reared up to 42 days of age in an intensive system (group I), as well as in a semi-intensive system (group II). In the 5th week of rearing, in the nutrition of group II, 30% of complete feed was replaced with wheat grain, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
3
16
0
1
Order By: Relevance
“…Maiorano et al (2017) reported an important sex effect in the final BW, carcass weight, carcass yield and pectoral muscle weight of Ross chickens slaughtered 42 d of age, higher in males than in females, but not in the carcass yield. Similar results were obtained by Kuźniacka et al (2014) in Hubbard-Flex chickens. Differently, Lopez et al (2011) found that male broilers had a higher final BW, carcass weight, and PM weight and lower carcass and breast meat yields when compared with females.…”
Section: Live Body Weight and Slaughter Performancesupporting
confidence: 88%
See 2 more Smart Citations
“…Maiorano et al (2017) reported an important sex effect in the final BW, carcass weight, carcass yield and pectoral muscle weight of Ross chickens slaughtered 42 d of age, higher in males than in females, but not in the carcass yield. Similar results were obtained by Kuźniacka et al (2014) in Hubbard-Flex chickens. Differently, Lopez et al (2011) found that male broilers had a higher final BW, carcass weight, and PM weight and lower carcass and breast meat yields when compared with females.…”
Section: Live Body Weight and Slaughter Performancesupporting
confidence: 88%
“…Many authors provide conflicting information concerning the effect of rearing system on dressing percentage and carcass cutting yields. Kuźniacka et al (2014) did not indicate any effect of rearing system (intensive vs. semi-intensive) on dressing percentage in Hubbard-Flex broilers. Instead, Skomorucha et al (2008) reported a higher carcass yield in 42-d-old Cobb broilers housed without outdoor access compared to birds grown with outdoor access.…”
Section: Live Body Weight and Slaughter Performancementioning
confidence: 64%
See 1 more Smart Citation
“…Carcass and meat quality in broiler poultry depends on many parameters, including genotype, sex, age, and diet. In the composition of feeds, the content of total protein affects the nutritive value of muscle tissue [1]. Most broiler geese produced in Poland are two-strain crossbreeds designated W31 (White Kołuda ® geese) and they make up over 95% of the local population.…”
Section: Introductionmentioning
confidence: 99%
“…The quality and quantity of muscle tissue in the carcass of birds depend on the composition of feed used in their diet. The diet of young oat geese (commercial: White Kołuda ® geese) should contain 22.0-15.0% of crude protein and 12-11.7 MJ of metabolizable energy (ME) [3][4][5][6]. These geese are a crossbreed (W31) of two strains (W11 × W33) and characterized by a good quality of meat and fat in carcasses, which adds to the flavor of meat [1].…”
Section: Introductionmentioning
confidence: 99%